Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1182/bloodadvances.2019001409
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of deep vein thrombosis of the upper extremity: a systematic review and meta-analysis of test accuracy

Abstract: Upper extremity deep vein thrombosis (UEDVT) accounts for ≤10% of DVT and can be associated with morbidity and mortality. Accurate diagnosis and treatment are necessary for safe and effective patient management. We systematically reviewed the accuracy of D-dimer and duplex ultrasonography (US) for the evaluation of suspected first-episode UEDVT. We searched the Cochrane Central Register, OVID MEDLINE, EMBASE, and PubMed for eligible studies, reference lists of relevant reviews, registered trials, and relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The final recommendations for a diagnostic pathway were based on information provided in this review on patient-centered outcomes and based on information provided in the test accuracy review. [2][3][4] In addition to these reviews, the panel considered information on the overall certainty in the evidence, including certainty in the diagnostic test accuracy results, patients' values and preferences, balance of desirable and undesirable effects, resource implications, feasibility, acceptability, and equity considerations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The final recommendations for a diagnostic pathway were based on information provided in this review on patient-centered outcomes and based on information provided in the test accuracy review. [2][3][4] In addition to these reviews, the panel considered information on the overall certainty in the evidence, including certainty in the diagnostic test accuracy results, patients' values and preferences, balance of desirable and undesirable effects, resource implications, feasibility, acceptability, and equity considerations.…”
Section: Discussionmentioning
confidence: 99%
“…9 The primary source of information was obtained from the studies that were included for the analysis of test accuracy, represented in Figure 1 and discussed in a separate paper. 3,4 The secondary source included studies identified as having potential information for outcomes when the initial search was completed, regardless of whether the study contained test accuracy information. The final source was any additional studies suggested by experts in the field or other guidelines.…”
Section: Data Sources and Searchesmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] The elevation of d-dimer levels is considered nonspecific as d-dimers are markers of clot degradation and are acute phase reactants often elevated in inflammatory states not necessarily associated with hypercoagulability. 8 Conventional coagulation tests are usually not abnormal in the presence of clinical hypercoagulability. For example, patients with liver disease often have abnormal conventional coagulation tests such as an elevated international normalized ratio 9 or decreased platelets 10 indicating hypocoagulability but may exhibit normal or even increased thrombin formation.…”
mentioning
confidence: 99%
“…While the reference imaging standard for UEDVT diagnosis is assumed to be venography, 18 this has been extrapolated from lower limb DVT studies where it is the reference standard. In idiopathic UEDVT there are no studies where patients with suspected thrombosis and negative venography are followed for 90 days to confirm no subsequent diagnosis of UEDVT is made.…”
mentioning
confidence: 99%